Modern Mosque Architecture and its Impact on Islamic Identity: A Study of Mosques in European Countries - Sudarmadi Putra; Tamer Youssef; Dina Ahmed; Jasafat Jasafat (Journal of Noesantara Islamic Studies, 2025)
The increasing presence of Islam in Europe has led to the emergence of modern mosque architecture, raising questions about its impact on Islamic identity. This study examines how modern architectural styles influence the perception and experience of Islamic identity within European Muslim communities. This research aims to analyze the architectural features of selected modern mosques in Europe and explore how these features interact with the construction and negotiation of Islamic identity among worshippers. Employing a qualitative research methodology, this study conducts case studies of several prominent modern mosques in various European countries. Data collection involves site visits, architectural analysis, and semi-structured interviews with mosque attendees and community leaders. The study analyzes the interplay between modern architectural aesthetics, traditional Islamic architectural elements, and the evolving interpretations of Islamic identity in a European context. Some mosques prioritize minimalist designs and contemporary materials, while others incorporate subtle Islamic motifs within modern frameworks. The study concludes that modern mosque architecture in Europe serves as a dynamic space where Islamic identity is negotiated and expressed in diverse ways, reflecting the complex interplay between tradition, modernity, and the specific socio-cultural contexts of European Muslim communities.